PENGARUH KEPATUHAN WAJIB PAJAK, PEMERIKSAAN PAJAK, PENAGIHAN PAJAK, DAN KEGIATAN SOSIALISASI PERPAJAKAN TERHADAP PENINGKATAN PENERIMAAN PAJAK PENGHASILAN BADAN (Studi Empiris Pada Kantor Pelayanan Pajak Pratama Pekanbaru Tampan) - Afrina Setiawati; Raja Adri Satriawan; Volta Diyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The objective of this research was to analyze the influence of taxpayer compliance, tax audit, tax collection, and tax socialization toward the increase of corporate income tax receivable. The population in this research is the company registered in the tax office of Pratama Tampan Pekanbaru from 2014 until 2016. Sample was determined by the jenuh sampling method. The data type that being used in this research were quantitative data by using monthly secondary data, while the method of analysis used is multiple regression analysis and use SPSS version 19.00 as the software for processing the data. The test results of this study indicate that the taxpayer compliance, tax audit, and tax collection effect the increase of corporate income tax receivable. Meanwhile, tax socialization have no effect on the increase of corporate income tax receivable. Based on the total adjusted R-square results proved that the independence variable, taxpayer compliance level, tax audit, tax collection, and tax socialization affect the increase of corporate income tax receivable of 0.775 or 77.5%. While the remaining 22.5% is explained by other variables that are not performed in this research.Keyword : taxpayer compliance, tax audit, tax collection, tax socialization, income tax receivable.